The law of nature conservation - Rodgers, C. P. (Christopher P.) (Oxford : Oxford University Press, 2013)
This book provides a detailed account of the UK law of nature conservation. It covers all the extensive laws introduced in recent years to protect and promote the natural world, examining the operation of the legislation in practice.
Description based on online resource; title from home page (viewed on Apr. 5, 2013).
Includes bibliographical references and index.
Keywords: Nature conservation -- Law and legislation -- Great Britain